The Facial Width-To-Height Ratio is Unrelated to Aggressive Behaviour in Indonesian People - Muhammad Isa Ananta; Andy Darmawan; Sarah Nila; Kanthi Arum Widayati (Bogor Agricultural University, Indonesia, 2023)
As a channel of non-verbal communication, faces can give information such as mate attraction, intelligence, and aggressivity. Aggressivity is a character to dominate, protect position, and fight over resources. Several aggressive behaviours in humans are, for example, anger, hostility, physical aggression, and verbal aggression. Previous studies in western society showed that aggressivity could be perceived from the faces. We tested 100 Indonesian males ranging from 19-51 years old to fill out the Buss-Perry Aggression Questionnaire (BPAQ) to measure the aggression scale. The mean of their BPAQ scales (total aggression, anger, hostility, physical aggression, and verbal aggression) were 72.44±10.84, 17.37±3.97, 21.38±4.53, 18.97±4.65, 14.72±2.68, respectively. The average facial photograph was generated based on the min-Q1 (Low Aggressivity (LA)) and Q3-max (High Aggressivity (HA)) BPAQ scale. Next, the aggressivity of averaged LA and HA faces was evaluated by raters. The raters consisted of 145 males and 213 females randomly recruited, ranging from 17 to 67 years old. The facial width-to-height (fWHR) ratio between the average faces of the Low-Aggression face and the High-Aggression face was insignificant. This study concluded that Indonesian people could not perceive aggressivity in their faces.